Mechanisms of reduced sleepiness symptoms in heart failure and obstructive sleep apnea. (13th November 2018) - Pak, Victoria M.; Strouss, Lisa; Yaggi, Henry K.; Redeker, Nancy S.; Mohsenin, Vahid; Riegel, Barbara
Abstract: Patients with both heart failure and obstructive sleep apnea often have poor, repeatedly disrupted sleep, and yet they frequently do not complain of excessive daytime sleepiness. Understanding this lack of perceived sleepiness is crucial for the case identification and treatment of obstructive sleep apnea in the heart failure population at high risk of this disease, especially given the association between untreated obstructive sleep apnea and mortality among patients with heart failure. In this review, we present epidemiologic evidence concerning the lack of sleepiness symptoms in heart failure and obstructive sleep apnea, explore possible mechanistic explanations for this relationship, assess the benefits of treatment in this population, discuss implications for clinical practice and explore directions for future research.